Pure down-conversion photons through sub-coherence-length domain engineering. (12th July 2017) - Graffitti, Francesco; Kundys, Dmytro; Reid, Derryck T; Brańczyk, Agata M; Fedrizzi, Alessandro
Abstract: Photonic quantum technology relies on efficient sources of coherent single photons, the ideal carriers of quantum information. Heralded single photons from parametric down-conversion can approximate on-demand single photons to a desired degree, with high spectral purities achieved through group-velocity matching and tailored crystal nonlinearities. Here we propose crystal-nonlinearity-engineering techniques with sub-coherence-length domains. We first introduce a combination of two existing methods: a deterministic approach with coherence-length domains and probabilistic domain-width annealing. We then show how the same deterministic domain-flip approach can be implemented with sub-coherence-length domains. Both of these complementary techniques create highly pure photons, outperforming previous methods, in particular for short nonlinear crystals matched to femtosecond lasers.